Personalized sports recommendation systems using robotic-assisted techniques in urologic oncology recovery - Xue, Tongzhao; Shen, YaWen (Frontiers in Oncology, 2025)
IntroductionThe integration of robotic-assisted techniques in urologic oncology recovery has significantly improved surgical precision and patient outcomes. However, postoperative rehabilitation remains a crucial challenge, necessitating innovative approaches for enhancing physical recovery and quality of life. Personalized sports recommendation systems have emerged as a promising solution, leveraging sports analytics, machine learning, and biomechanical modeling to tailor rehabilitation exercises. Traditional methods rely on generalized rehabilitation protocols, often failing to consider individual patient conditions, recovery progress, and biomechanical constraints. These limitations hinder optimal rehabilitation and prolong recovery times.MethodsTo address these challenges, we propose a novel framework integrating robotic-assisted assessment with personalized sports analytics. Our approach utilizes a Dynamic Sports Performance Network (DSPN), which combines spatiotemporal data analysis, reinforcement learning, and real-time feedback mechanisms to optimize exercise recommendations. By incorporating multi-agent learning and predictive modeling, the system adapts rehabilitation plans based on patient performance, ensuring a tailored and effective recovery process. The system can integrate wearable sensor data and EMG signals to further refine exercise precision and monitor muscular responses in real time.ResultsExperimental evaluations demonstrate that our method significantly outperforms conventional rehabilitation strategies, offering higher precision in exercise recommendations, improved adherence rates, and enhanced recovery efficiency.DiscussionThis research provides a new direction in robotic-assisted rehabilitation, bridging the gap between sports science, intelligent systems, and urologic oncology recovery through interdisciplinary innovation and patient-centered design.